Enhancement of thermoelectric properties of p-type bismuth telluride bulk composites with AgTiO2 nano particles via spray coating and hot deformation process - Anil Kumar; Saurabh Thoravat; Hong Jong Jin; Junyoung Park; Hyungyu Jin; Pooja Rawat; Jong-Soo Rhyee (Journal of Materiomics)
We aimed to enhance p-type Bi0.4Sb1.6Te3.4 (BST) composite's thermoelectric (TE) properties by minimizing thermal conductivity through hierarchical phonon scattering via nano Ag-coated TiO2 (Ag/TiO2). Hot deformation (HD) was employed to induce multi-scale microstructures in these high-performance p-type TE materials, affecting electrical and thermal transport properties through improved textures and donor-like effects. Our optimization strategy included creating grain boundaries, multiple phonons scattering centers, and introducing high-density lattice defects, significantly reducing lattice thermal conductivity. The combined effects led to a noticeable improvement in the figure of merit (zT) across the temperature range, with all TE parameters measured along the in-plane direction. In the case of the hot-deformed Bi0.4Sb1.6Te3.4 alloy, the maximum zT reached 1.31 at 350 K, while the average zT (zTavg) was 1.17 in the range of 300–400 K, suggesting promising potential for near room temperature TE power generation and solid-state cooling.